PENGARUH DITERAPKANNYA E-FILING DALAM PERPAJAKAN DI ERA DIGITALISASI 4.0 TERHADAP KEPATUHAN MASYARAKAT DALAM MEMBAYAR PAJAK DI INDONESIA - Frendika, Eka (JURNAL PERPAJAKAN, 2023)
Tax is a contribution from the people to the state treasury based on law that can be enforced without receiving direct reciprocal services that can be shown and which are used to pay for general expenses". One f orm of digitalization 4.0 in the field of taxation is the submission of notification letters online called e- Filing. Based on the regulation of the Minister of Finance Number 181 / PMK03 / 2007, e-Filing is a method of submitting Annual Tax Returns which i s done online and in real time through the website of the Directorate General of Taxes (www.pajak.go.id) or Application Service Provider (ASP). With e- Filing, taxpayers will get convenience and save time and costs incurred because they can report Annual Tax Returns online 25 hours. Reviewed from the aspect of information technology in the current digitalization era, the implementation of e-filing is part of the implementation of electronic government (e -gov) in Indonesia